2022
DOI: 10.3390/bioengineering9050208
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Zero Dynamics Control for Gait Guidance of a Novel Adjustable Pediatric Lower-Limb Exoskeleton

Abstract: Exoskeleton technology has undergone significant developments for the adult population but is still lacking for the pediatric population. This paper presents the design of a hip–knee exoskeleton for children 6 to 11 years old with gait abnormalities. The actuators are housed in an adjustable exoskeleton frame where the thigh part can adjust in length and the hip cradle can adjust in the medial-lateral and posterior-anterior directions concurrently. Proper control of exoskeletons to follow nominal healthy gait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Previous evaluations indicated that the actuators were lightweight, low-friction, and easily backdrivable at the output, making them appropriate for use in a pediatric lower-limb exoskeleton [17]. These actuators were placed into an adjustable pediatric exoskeleton frame designed for children between 6 and 11 years old [18], resulting in the 4.72 kg exoskeleton shown in Figure 1. The ranges of adjustability were determined from estimated limb lengths and widths of children within the target age group, derived from anthropometric averages [47] and census data [48].…”
Section: Adjustable Pediatric Lower-limb Exoskeletonmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous evaluations indicated that the actuators were lightweight, low-friction, and easily backdrivable at the output, making them appropriate for use in a pediatric lower-limb exoskeleton [17]. These actuators were placed into an adjustable pediatric exoskeleton frame designed for children between 6 and 11 years old [18], resulting in the 4.72 kg exoskeleton shown in Figure 1. The ranges of adjustability were determined from estimated limb lengths and widths of children within the target age group, derived from anthropometric averages [47] and census data [48].…”
Section: Adjustable Pediatric Lower-limb Exoskeletonmentioning
confidence: 99%
“…The measurement convention for the human-exoskeleton system is shown in The ranges of adjustability were determined from estimated limb lengths and widths of children within the target age group, derived from anthropometric averages [47] and census data [48]. For a more detailed discussion of the exoskeleton device and joint actuators, see [17,18]. A preliminary human factor assessment with the unpowered adjustable pediatric exoskeleton and a healthy, 30.8 kg, and 149 cm tall child volunteer subject demonstrated that the hardware was comfortable, easily adjustable, and simple to don and doff [19].…”
Section: Adjustable Pediatric Lower-limb Exoskeletonmentioning
confidence: 99%
See 2 more Smart Citations
“…Exoskeletons offer modularity in design and implementation; some devices which target more affected individuals span the trunk and the legs, offering support at multiple joints and even can incorporate motorized walkers for support [ 15 , 16 ]. Exoskeletons which span multiple joints can also adapt the assistance strategy to the individual user, and recent efforts have focused on advanced control approaches to achieve this goal [ 17 20 ]. Other devices target single joints such as the ankle [ 21 ] or knee [ 22 24 ] in ambulatory individuals who walk with a gait pathology such as knee extension deficiency or drop foot.…”
Section: Introductionmentioning
confidence: 99%